Control Blood Sugar Levels of Children with Juvenile Diabetes with Creative Education - Lia Herliana; Hotma Rumahorbo (Health Notions, 2021)
Juvenile Diabetes (JD) is type diabetes I or Insulin Dependent Diabetes Mellitus (IDDM) which occurs in childhood, is hereditary due toreactions autoimmune in pancreatic beta cells. Damage to pancreatic beta cells results in the absence of insulin, leading to hyperglycemia and its complications. People with JD need insulin injections, dietary arrangements and physical exercise as well as emotional conditions that must always be maintained so that blood glucose remains balanced and avoid threatening acute complications. Acute complications such as hypoglycemia and diabetic ketoacidosis are the biggest threat for people with JD. This study aims to obtain an overview of changes in HbA1C levels in children with juvenile diabetes before and after creative education in both the intervention and control groups.research Quasi experimentaldesign pre post intervention with control group design. The research sample consisted of 42 students with JD, each of which consisted of 21 control groups and 21 intervention groups. The results showed a significant effect on the value of HbA1C levels before and after the intervention in the intervention group with p value = 0.02. Conclusion The creative application of education interventions can control blood glucose levels in children with JD, so it is recommended that these interventions be implemented especially in children with JD. Keywords: juvenile diabetes, creative education, HbA1C